The role of the African University in the Continent’s Development - Edoru, John Michael; Adebayo, Tajudeen Sanni (International Journal of Research in Education Humanities and Commerce, 2025)
This article deals with the role of African universities and higher education institutions in the development of the continent. Knowledge production is the responsibility of higher education institutions. Knowledge can only be useful it can be used for the wellbeing of humanity. African governments therefore, believe that investing in higher education and producing many university graduates is a gateway to their development. In most cases, these governments forget about the need to churn out the personnel that is crucial for their development and produce them just for the sake of it. The notion of having many university graduates as a means to achieve the country’s development is therefore in balance since the universities produce graduates of all cadre. Some of these may be unemployable and may not meet the current needs of the society. Most of the businesses, government parastatals, educational institutions, and ministries heavily rely on manpower that is a product of a university or a higher institution of learning. Without knowledge production, it is impossible to talk about the achievement of the Millenium Development Goals which many countries are hoping for by the year 2025.In these goals, the emphasis is put on poverty eradication, education for all, health for all, food security for all among others. The important question therefore that this paper attempts to answer is as to whether African universities actually play an important role in providing the required knowledge that Africa and the world badly require for development. The paper will scan through the continent’s major universities and attempt to make an assessment of the impact in terms of knowledge and contributions that these universities are making to Africa’s development. Governments in Africa need to look at their needs in terms of the priorities to bolster their development and gear their curricular towards meeting those priorities.